American Clinical Neurophysiology Society Guideline 5: Minimum Technical Standards for Pediatric Electroencephalography. Issue 4 (August 2016) - Kuratani, John; Pearl, Phillip L.; Sullivan, Lucy; Riel-Romero, Rosario Maria S.; Cheek, Janna; Stecker, Mark; San-Juan, Daniel; Selioutski, Olga; Sinha, Saurabh R.; Drislane, Frank W.; Tsuchida, Tammy N.
Abstract : Summary: This revision to the EEG Guidelines is an update incorporating the current electroencephalography technology and practice. It was previously published as Guideline 2. Similar to the prior guideline, it delineates the aspects of Guideline 1 that should be modified for neonates and young children. Recording conditions for photic stimulation and hyperventilation are revised to enhance the provocation of epileptiform discharges. Revisions recognize the difficulties involved in performing an EEG under sedation in young children. Recommended neonatal EEG montages are displayed for the reduced set of electrodes only since the montages in Guideline 3 should be used for a 21-electrode 10-20 system array. Neonatal documentation is updated to use current American Academy of Pediatrics term "postmenstrual age" rather than "conceptional age." Finally, because therapeutic hypothermia alters the prognostic value of neonatal EEG, the necessity of documenting the patient's temperature at the time of recording is emphasized.